History unveiled: Theological perspectives from St John"s Revelation - Mihoc, Daniel (HTS teologiese studies, 2023)
This article aims to highlight St John’s peculiar perspectives on the meaning and the consequences of Christ’s sacrificial death for our apparently evil-dominated history and to bring a new light on the mystery of evil the Book of Revelation speaks about. My analysis begins with St John’s Christocentric perspective on history, continues with the significance of its driving forces revealed in the vision of the seals and ends with an evaluation of the evil triad, which tries to stop the unfolding of the salvific work of God. Alongside Christ, Christians play an essential role in the conflict with these powers and, thus, in transforming the world according to God’s plan. The outcome of this conflict does not depend on which side has more power, as one may conclude under the effect of the violent imagery of the book, but on the Lamb’s blood’s lasting effects, which enable each Christian to become a conqueror, sharing in his Lord’s victory.Contribution: This article highlights some of the contributions of the Book of Revelation to a Christian theology of history and argues that the main point is the overwhelming value of Christ’s blood and its reception for the much expected victory over evil. To transform the world, the victory won by Christ has to be actualised by each of his followers.